SOSIALISASI ANAK DAN MELEMAHNYA TRADISI DALAM MIGRASI INTERNASIONAL: KASUS TKW DARI GODONG GROBOGAN JAWA TENGAH - Tri Marhaeni P. Astuti (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2009)
International migration that women from Godong , Grobogan, CentralJava, did has brought about social, cultural, political, and economic changes.This paper focuses on the social changes that these migrant women have caused to their family and the society. These social changes were viewed from local and global points of view, suggesting the loosening of traditional values and the evaluation of family relationship. In-depth interviews with a sample of the women in both Grobogan and Malaysia showed that there was a shift of the values of daughters, and the weakening of traditional social values. The family was found not to be the main control centre in the family life cycle anymore, but the daughters were. The separation of the women from their children suggests the weakening